2013
DOI: 10.13169/worlrevipoliecon.4.4.0508
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Factors that Influence the Utilization Rate of Renewable Energy in the Framework of Marxist Reproduction

Abstract: Developing the renewable energy to replace traditional fossil energy is not only an essential part of sustainable development strategies of most countries all over the world, but also an important theoretical issue that draws the attention of the academic circle. On the basis of a Marxian reproduction scheme, the essay analyzes the influence of market demand, technological progress and policy promotion on the utilization rate of renewable energy and their mechanisms during the development of the renewable ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…These results are supported by a study by Ma et al (2013) in 28 OECD countries, which show that one factor might have a positive effect in one case and a negative one in others. Furthermore, these results are consistent with findings in Uganda by Asada (2019) and in Thailand by Dunn et al (1982) that low calorific value for waste charcoal was suitable in rice cooking and steaming banana, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These results are supported by a study by Ma et al (2013) in 28 OECD countries, which show that one factor might have a positive effect in one case and a negative one in others. Furthermore, these results are consistent with findings in Uganda by Asada (2019) and in Thailand by Dunn et al (1982) that low calorific value for waste charcoal was suitable in rice cooking and steaming banana, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…This research revealed that public policies and institutions did not impact waste charcoal utilization (p = 0.321) and Cramer's v value (v = 0.058. These findings contradict those from Ma et al (2013), Zahabu (2008), andDoggart et al (2020), which showed that government policies were the most important factor in improving the utilization of energy in low-income countries. The contradiction is mainly due to the enforcement of rules and guidelines according to the Government Notice (Forest Royalty Collection).…”
Section: Discussionmentioning
confidence: 61%